Edenic Children and Unripened Fruit: Anthropological and Botanical Immaturity in the Ethiopic Mystery of the Judgment of Sinners - Bonar, Chance E. 1993- (2024)
In the late thirteenth or early fourteenth century, scribes around Lake Tana in northwestern Ethiopia translated and disseminated an Arabic apocryphal dialogue between Jesus and Peter. Recording exhortations and revelations meant to be passed on to Clement of Rome and other apostolic figures, the Mystery of the Judgment of Sinners (Myst. Sinners) contains a little-explored retelling of Genesis 2-3. In its rendition of the Adam and Eve’s time in the Garden of Eden, Jesus explains to Peter how commandment not to the tree of the knowledge of good and evil was a test of their patience. In particular, Adam and Eve are marked as "children" and the fruit in terms of its "ripeness" or lack thereof. Here, I want to contextualize this claim of a dual immaturity between both the humans and plants in the Garden of Eden in terms of early Christian theological claims about the youth and imperfection of Adam and Eve.